Analisis Pemanfaatan E-Commerce dan Digital Marketing sebagai Pendorong Produktivitas UMKM di Kota Kupang - Maria Lusia Mutiara Lori; Ronli Anugrah Amnifu; Osoroi Maryano Sombai; Yohanes Pemandi Lian (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid growth of digital technology has transformed business practices among MSMEs, particularly through the adoption of e-commerce and digital marketing. However, the level of digital literacy and the ability of business actors to optimize digital platforms in Kupang City remain uneven, creating a gap between available technological opportunities and their actual utilization. This study aims to analyze how MSMEs in Kupang City employ e-commerce and digital marketing and how these practices contribute to business productivity. Using a qualitative method with an analyticalexploratory approach, data were collected through in-depth interviews, observation, and documentation. The data were analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, presentation, and conclusion verification. The findings indicate that e-commerce enhances business visibility, accelerates transactions, and expands market reach, especially for MSMEs with higher digital competence. Digital marketing through social media platforms also strengthens customer engagement when content is produced consistently and reflects local cultural nuances. The most substantial improvement in productivity appears among MSMEs that integrate e-commerce and digital marketing, resulting in increased sales, broader customer reach, and more efficient operations. Nevertheless, limited digital literacy, inadequate equipment, and weak content management remain obstacles for many business actors. These results underscore the need to strengthen digital capacity so that MSMEs in Kupang City can fully utilize digital opportunities and enhance their competitiveness.